Essential oils for the postharvest control of blue mold and quality of ’Fuji’ apples - Vieira, Amanda Maria Furtado Drehmer; Steffens, Cristiano André; Argenta, Luiz Carlos; do Amarante, Cassandro Vidal Talamine; Oster, Andreia Hansen; Casa, Ricardo Trezzi; Amarante, Antônio Gabriel Mortari; Pansera-Espíndola, Bruno (Pesquisa Agropecuaria Brasileira, 2018)
The objective of this work was to evaluate the effect of rosemary, cinnamon, citronella grass, and clove essential oils on the in vitro growth of Penicillium expansum, on the diameter of blue mold lesions, and on the physical and chemical attributes of 'Fuji' apples stored under refrigeration for different periods of time. The compositions of the essential oils were determined, and their effects on the growth inhibition, number, and viability of fungal spores in vitro were evaluated at 0, 100, and 1,000 μL L-1 oil concentrations. At postharvest, evaluations were performed for fruit treated with 0, 50, 100, and 500 μL L-1 essential oil and kept under refrigeration for 30 days, and for fruit treated with 0, 100, and 500 μL L-1 oil and kept under refrigeration for two days. The essential oils – eucalyptol (rosemary), eugenol (cinnamon), citronellal (citronella), and eugenol (clove) – reduce the growth, number, and viability of P. expansum spores 24 hours after the induction to germination, as well as the diameter of blue mold lesions in apples, except for citronella oil at 500 μL L-1 after 30 days of cold storage. There are no changes in the physicochemical attributes of apples, treated with different concentrations of the oils after refrigeration for five months, followed by seven days at room temperature.